A Data Model and Processing Environment for Ocean-Wide Bathymetric Data Compilations - Hell, Benjamin; Jakobsson, Martin (The International Hydrographic Review, 2008)
The compilation of ocean-wide digital bathymetric models (DBM) requires specific features of the bathymetric data storage and great flexibility of the data processing chain. In this article a solution based upon a spatial relational database management system and a Geographical Information System front end is introduced, which will eventually serve the compilation of a new DBM of the North Atlantic Ocean. As shown in a preliminary case study, the abundance of sounding data-both single beam and multibeam-available in that area to date bears an extremely high potential to derive a DBM with much greater accuracy and resolution than the DBMs commonly used today.